"My Story Came to Life!": How Multimodality Can Inspire Revision in Writing. Issue 3 (July 2018) - Batchelor, Katherine
Revision has been studied mostly from a language centric viewpoint. It is an understudied topic and oftentimes viewed as an afterthought in classrooms rather than a central facet at the heart of quality writing. The focus of this article is on teaching revision via multimodality as a way to serve all students, especially gifted students. This article highlights 27 gifted students' multimodal artifacts and discussions about the revision process in writing when paired with multimodality. The premise is that teaching revision using multiple modes of communication can lead to deeper, abstract thinking, where students can visualize their writing, thus leading to more revision choices. It is hoped that teachers can routinely use this strategy during writing instruction.